Utilization of information technology as a business means for the Sugihmas Village Community - Endah Ratna Arumi; Ahmad Fauzi; Fani Chairul Handoko; Kevin Syahidan Ananda; Talitha Ayu Pramudyanti; Intan Meganingrum (Universitas Muhammadiyah Magelang, 2023)
This community service activity focuses on the use of information technology to do business and market products belonging to the residents of Sugihmas village. Activities are carried out through training and mentoring. The result of this activity is the utilization of e-commerce and social media applications for marketing activities that can cover a wider market. With this information technology use training program, it is hoped that it will be able to improve the economic quality of the Sugihmas villagers through product innovation from plastic waste recycling and strengthening digital marketing.